Amtsal dalam Ayat-Ayat Surga dan Neraka - Samsul Bahri; Hilal Refiana (TAFSE: Journal of Qur'anic Studies, 2017)
The Qur'an is one of the eternal miracles and is used to challenge the disbelievers. One of the miraculous aspects of the Qur'an is the beauty of language. Amtsal or tamtsil is one of the uslub of the Qur'an in expressing various explanations in terms of its miracles. Matsal means equating something with several related things. However, matsal is not just an equation, it is a parable that is gharib in the sense of astonishing or surprising. The main problem in this discussion is on the one hand in the Qur'an it is stated that knowledge of the occult is only known by Allah. But on the other hand in a number of verses of the Qur'an, there are descriptions or parables about heaven and hell which basically include the unseen through the verses of amtsal. This discussion is studied using the maudhu'i (thematic) method through library research in the form of content analysis. The Qur'an describes heaven in various ways, generally by giving a material description and accompanied by spiritual pleasures of a spiritual nature. By often including the mention of the attributes of heaven and the attributes of hell, it is hoped that people will be happy (hope) with heaven and avoid (fear) hell. Al-Qur’an merupakan salah satu mukjizat yang kekal dan dipergunakan untuk menantang orang-orang yang ingkar. Salah satu segi kemukjizatan al-Qur’an adalah keindahan bahasa. Amtsal atau tamtsil merupakan salah satu uslub al-Qur’an dalam mengungkapkan berbagai penjelasan dari segi kemukjizatannya. Matsal diartikan mempersamakan sesuatu dengan beberapa hal yang saling berkaitan. Namun, matsal bukan sekedar persamaan, ia adalah perumpamaan yang gharib dalam arti menakjubkan atau mengherankan. Pokok masalah dalam pembahasan ini adalah di satu sisi dalam al-Qur’an disebutkan bahwa pengetahuan tentang persoalan gaib hanya diketahui oleh Allah. Namun di sisi lain dalam sejumlah ayat al-Qur’an terdapat penggambaran atau perumpamaan tentang surga dan neraka yang pada dasarnya termasuk hal gaib melalui ayat-ayat amtsal. Pembahasan ini dikaji dengan metode maudhu’i (tematik) melalui kajian kepustakaan (library research) yang berbentuk analisis isi (content analysis). Al-Qur’an menjelaskan tentang surga dengan berbagai cara, yang umumnya dengan memberikan gambaran yang bersifat material dan disertai dengan kenikmatan rohani yang bersifat spiritual. Dengan sering menyertakan penyebutan sifat-sifat surga dan sifat-sifat neraka, diharapkan agar manusia senang (berharap) dengan surga dan menghindari (takut) akan neraka.